(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The article describes the main features and functions of Google Docs, in particular Document, Presentation, Table, Form. It is shown the specific features of using this service for teaching future teachers of mathematics to solve information problems: finding information of various types to carry out joint projects. It is suggested the three stage of technique of management of collective work for mastering Google Docs in learning and further professional activity of future teachers of mathematics. In the first stage, students become familiar with Google Docs as a users and learn how to use its various features on the example of solving of widely distributed problems.In the second stage, having the skills of the user, the students use the tools as pupils for solving problems in mathematics. At the third stage, students consider the service as teachers to resolve methodological and organizational professional tasks of teachers of mathematics. It is analyzed the results of using Google Docs at computer science classes in training of bachelors (6.040201 Mathematics) at Kharkiv National Pedagogical University named after G.S. Skovoroda.